The perception of integrity of three public agencies in Kuala Terengganu - Ismail, Rusnah; Ngah, Nazlin Emieza; Abdullah, Iskandar Hasan Tan; Salleh, Asri; Ibrahim, Norlaila; Ahmad Tajuddin, Nur Hafizah; Jusoff, Kamaruzaman; Mat Zin, Sakinah (IDOSI Publications, 2011)
Malaysia in its effort to become a fully developed nation by 2020 has undertaken a monumental task in instilling noble values into its society including its civil sector. The integrity of the civil servants needs to be greatly improved in order to turn this vision into a reality. This project attempted to examine the level of awareness, knowledge and understanding on noble values particularly integrity among selected civil servants in selected State Government agencies in Terenganu, Malaysia. The respondents were selected based on a purposive sampling technique. The research used a quantitative approach where self-administered structured questions were distributed. Descriptive and inference analysis were carried out to meet the research objectives outlined. The research findings showed that there were civil servants groups who were unclear and uncertain about the meaning of integrity in public sector. Those with shorter length of services were found to be less knowledgeable on the rule and procedure which led to them being unsure about integrity. Length of service was found to be inversely related to the perception on the knowledge of integrity, corruption and quality of service delivery. For that reason, future research should identify the causes that will lead to enhancement of perception of integrity.